Yield of Syn-1 synthetic varieties of tropical onion resulting from openpollinated Brazilian populations - Alves, Ítala Layanne de Souza; Oliveira, Valter Rodrigues de; Fernandes Santos, Carlos Antonio (Comunicata Scientiae, 2023)
Due to technological limitations for the development of onion hybrids, first-cycle synthetic varieties (Syn1- SV) could be an alternative to partially explore heterotic vigor. The growing areas of onion hybrids in Brazil are mainly defined by bulb yield and uniformity. From this perspective, the present study aimed to develop tropical onion Syn1-SV and estimate mid-parent heterosis (Hm), heterobeltiosis (Hp), and standard heterosis (Hs) as an alternative to hybrid development. Six Syn1-SVs, eight open-pollinated (OP) populations, and one commercial hybrid were evaluated in a randomized block design with three replications, in two semesters, for the commercial bulb yield (CBY) and days to bulb harvest (DBH). Significant differences were observed for treatments (T), semesters (S) and the T*S interaction for both variables (p-value<0.05). The OPs ‘Alfa SF RT’ in the first semester and ‘IPA11’ in the second semester were the most precocious treatments. The highest CBY was estimated in the commercial hybrid (105.8 t ha-1) and in ‘Alfa SF RT’ (45.5 t ha-1) in the first and second semesters, respectively. Three Syn1-SVs showed positive Hm values, ranging from 2.0% to 6.3% for CBY. Three Syn1-SV showed positive Hp values in the first semester, ranging from 3.0% to 5.2%, for CBY. Only the Syn1-SV ‘Alfa SF RT’ × ‘BRS Alfa São Francisco’ (48.9 t ha-1) showed positive Hs values, surpassing by a small value the control OP population ‘IPA11’ (48.0 t ha-1), indicating the potential of Syn1-SV as an option for onion hybrids.